Pendampingan Kualitas Layanan kepada Minimarket Credit Union Lestari Dharma Yogyakarta - Septiari, Elisabet Dita; Francoise, Jeanne (Civiliza Publishing, 2024)
Credit Union Lestari Dharma is one of the cooperatives in Sleman, which has expanded its business from saving and loans into a minimarket business. As a new business, the management of minimarkets needs assistance with how to manage minimarkets so that many consumers come and buy, make profits and survive. The service activity toward minimarket is carried out by providing assistance to the manager and employee of minimarket CU Lestari Dharma in order to improve the quality of service. The material of assistance is SCORE (Sustaining, Competitive, and Responsible Enterprises) and marketing. The method of assitance is training, coaching, and evaluating, which lasts for three months from September to November 2024. The results of training and assistance for minimarket Lestari Dharma are increasing in efficiency of product finding and servicing, increasing in number of product sales, and smoother communication between managers. Overall, this activity have a positive impact on minimarket in increasing productivity and profitability. The continuous implementation of this initiative will help maintain and improve the performance of cooperatives.